Pengaruh Kecakapan Manajerial Terhadap Praktik Manajemen Laba Dengan Corporate Governance Sebaga Variabel Pemoderasi - Annas Budi Wicaksono; Etna Nur Afri Yuyetta (Diponegoro Journal of Accounting, 2013)
The purpose of this research is to examine the influence of managerial capability on earning management. This research also examines the role of corporate governance, comprising of the proportion of independent commissioner board, institutional ownership and managerial ownership in moderating the influence of managerial capabilities towards earning management. This research uses secondary data of 42 manufacturing companies that are listed in Indonesian Stock Exchange and published annual report from 2009-2011. This research measures managerial capabilities using Data Envelopment Analysis (DEA). Earning management is measured using modified Jones Model. This research uses multiple linear regressions to test the effects of managerial capabilities on earning management. It consists of two regression models (using moderating variable: corporate governance; the proportion of independent commissioner board, institutional ownership and managerial ownership). The result of this research shows that managerial capabilities are significantly influence earning management. It also shows that the proportion of independent commissioner board, institutional ownership and managerial ownership are unable to moderate the influence of management capabilities on earning management.